The Thin loop apposition as a method filling of digestive tract gaps: anatomopathological colaboration Br. L. E. Bueno - Mesa Figueras, Guillermo; Martínez Platero, Raúl; Lizazo, Isabel; Campos, Enrique (Cirugía del Uruguay, 2021)
The small loop apposition technique is useful and the results in the experimental field are excellent. It is applicable to any part of the digestive tract. In the case of animals with important metabolic unbalance and adverse local conditions it is an effective procedure.